(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The subject of researches are the regularities of the effective operation of information, resource and energy saving technology for the gases utilization from coal mines and metallurgical industries. The aim of the work is to present the technical and economic aspects of the information resource and energy saving process for the gases utilization from coal deposits and mines. As the result, the information about a new method for increasing the accuracy of automated commercial metering of coal gas, supplied to the Ukrainian gas-transport system, was provided, the regularities, governing the energy efficiency of controlling of the air/gas ratio from the oxygen concentration in the flue gases of the boiler unit, and the criterion of energy-efficient management were established. The calculation of the expected annual economic effect from the implementation of the control station “DIYA”, using the presented developments, was given.